INTERNATIONAL COOPERATION AMONG STATES IN GLOBALIZED ERA:THE DECLINE OF STATE SOVEREIGNTY - Koesrianti, Koesrianti (UI Scholars Hub, 2013)
This article discusses the national sovereignty and regionalism in the context of the membership of a state into regional economic organisations. It concludes that in nowadays-shrinking world the traditional concept of sovereignty is less relevant since states have suffered a loss in their sovereignty. It found that member states of regional economic organisations have to cede a degree of sovereignty, such as in the EU. This phenomenon however is not the case for NAFTA and AFTA.